2012
DOI: 10.1371/journal.pone.0033605
|View full text |Cite
|
Sign up to set email alerts
|

The Twin-Arginine Translocation Pathway in α-Proteobacteria Is Functionally Preserved Irrespective of Genomic and Regulatory Divergence

Abstract: The twin-arginine translocation (Tat) pathway exports fully folded proteins out of the cytoplasm of Gram-negative and Gram-positive bacteria. Although much progress has been made in unraveling the molecular mechanism and biochemical characterization of the Tat system, little is known concerning its functionality and biological role to confer adaptive skills, symbiosis or pathogenesis in the α-proteobacteria class. A comparative genomic analysis in the α-proteobacteria class confirmed the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Prior analyses focusing on bacteria (Dilks et al ., 2003) and Alphaproteobacteria (Nunez et al ., 2012) reported Tat systems of Rickettsia spp. lacking TatB proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior analyses focusing on bacteria (Dilks et al ., 2003) and Alphaproteobacteria (Nunez et al ., 2012) reported Tat systems of Rickettsia spp. lacking TatB proteins.…”
Section: Discussionmentioning
confidence: 99%
“…lack a gene encoding the TatB protein (Dilks et al ., 2003, Nunez et al ., 2012) . A study on the Tat system of Anaplasma marginale revealed the expression of tatA , tatB and tatC , as well as the ability of recombinant TatA and TatB (but not TatC) to restore Tat function in E .…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on the twin-arginine translocation (Tat) pathway of Anaplasma marginale also shows the ability of its component genes to retain function in cross-species complementation using E. coli (43). RT0216 transcript expression during R. typhi infection in HeLa cells suggests that its encoded protein may play a role in R. typhi growth and pathogenesis (5).…”
Section: Figmentioning
confidence: 99%